War Gaming Peace Operations. (February 2013) - Mason, Roger; Patterson, Eric
Today's military personnel fight against and work with a diverse variety of nonstate actors, from al-Qaeda terrorists to major nongovernmental organizations who provide vital humanitarian assistance. Furthermore, the nontraditional battle spaces where America and its allies have recently deployed (Kosovo, Afghanistan, Iraq) include a wide range of activities quite different from classic military campaign. How can the United States and its allies train its military personnel to think through the intersection of issues regarding working alongside and against nonstate actors, particularly in culturally sensitive environments? This article describes one such approach, the development of a war game for peace, designed for U.S. military officers and now utilized in the classrooms of several military colleges. More specifically, the article describes how reconstruction and stabilization operation decisions are modeled and worked through in the highly religious environment of contemporary Afghanistan through the use of an innovative board game, suggesting that this model can be applied to many other scenarios and classroom environments.